2015
DOI: 10.1002/anie.201507328
|View full text |Cite
|
Sign up to set email alerts
|

Strong, Thermally Superinsulating Biopolymer–Silica Aerogel Hybrids by Cogelation of Silicic Acid with Pectin

Abstract: Silica aerogels are excellent thermal insulators, but their brittle nature has prevented widespread application. To overcome these mechanical limitations, silica-biopolymer hybrids are a promising alternative. A one-pot process to monolithic, superinsulating pectin-silica hybrid aerogels is presented. Their structural and physical properties can be tuned by adjusting the gelation pH and pectin concentration. Hybrid aerogels made at pH 1.5 exhibit minimal dust release and vastly improved mechanical properties w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
108
0
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(129 citation statements)
references
References 44 publications
9
108
0
12
Order By: Relevance
“…The NFC scaffold improved the mechanical properties of silica aerogels and resulted in interpenetrating hybrid aerogel networks having low density (0.12-0.14 g/cm 3 ), high porosity (>93%) and high specific surface area (450 m 2 /g). In addition, the same research group has synthesized strong aerogels based on silica-pectin hybrid matrices, in which the pectin was incorporated in the silica network through a controlled parameter one-pot synthesis approach [177].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The NFC scaffold improved the mechanical properties of silica aerogels and resulted in interpenetrating hybrid aerogel networks having low density (0.12-0.14 g/cm 3 ), high porosity (>93%) and high specific surface area (450 m 2 /g). In addition, the same research group has synthesized strong aerogels based on silica-pectin hybrid matrices, in which the pectin was incorporated in the silica network through a controlled parameter one-pot synthesis approach [177].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…[7] This step is particularly important so as to prevent collapse of the pores if they are only af ew nanometers in size,orifthe solid network is not rigid enough. [11] Another class of organic aerogels comprises high-molar-mass semicrystalline polymers.S uch materials are obtained from entangled dilute solutions that undergo physical gelation upon crystallization of polymer segments.Alarge variety of hydrophilic polymer based aerogels,o ften derived from biomass,h as been studied over the years. Thus,t hey lead to aerogels with lower surface areas,i nt he range 10-500 m 2 g À1 ,a nd with at endencyt oh ave al arger and hierarchical distribution of pore sizes,typically mesopores in the 5-50 nm range,but also larger macropores over 50 nm.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Decreasing heat transfer through better insulation is probably the most important factor to improve the energy efficiencyo f buildings and there is an eed to develop materials with asuperior insulation performance compared to commercially available polymeric insulation materials,s uch as expanded polystyrene (EPS) and inorganic insulating materials,such as glass wool. [5] However,addition of inorganic fillers to an organic material increases the density and can make the hybrid more fragile.Poor compatibility between the inorganic fillers and the polymer matrix can also result in catastrophic disintegration during combustion and fail to prevent thermally induced collapse of the building. [3] Unfortunately,m any of the commonly used flame retardants are halogenated or phosphorous compounds with potential impacts on the environment and human health, especially the brominated flame retardants which will generate neurotoxic and potentially carcinogenic brominated furans and dioxins.…”
mentioning
confidence: 99%
“…[2] Thermally insulating materials also have to be fire retardant and mechanically resilient or flexible.P olymeric insulation materials are often flexible but easily ignitable and can sustain and rapidly spread af ire in the absence of fire barriers.The fire retardant properties of polymeric insulation materials,s uch as EPS,c an be improved by the addition of flame retardants. [5] However,addition of inorganic fillers to an organic material increases the density and can make the hybrid more fragile.Poor compatibility between the inorganic fillers and the polymer matrix can also result in catastrophic disintegration during combustion and fail to prevent thermally induced collapse of the building. [4] Recent work has shown that the flame retardant properties of organic-inorganic composites can be significantly improved by the addition of well-distributed inorganic fillers, such as carbon nanotubes,s ilica, layered montmorillonite (MMT), needle-like sepiolite and metal oxides or hydroxides (e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation